Detection and immunolabeling of peroxisomal proteins - Schrader, Tina A.; Islinger, Markus; Schrader, Michael (Peroxisomes, 2017)
Peroxisomes are essential organelles in mammals which contribute to cellular lipid metabolism and redox homeostasis. The spectrum of their functions in human health and disease is far from being complete, and unexpected and novel roles of peroxisomes are being discovered. To date, those include novel biological roles in antiviral defence, as intracellular signaling platforms and as protective organelles in sensory cells. Furthermore, peroxisomes are part of a complex network of interacting subcellular compartments which involves metabolic cooperation, cross-talk and membrane contacts. As potentially novel peroxisomal proteins are continuously discovered, there is great interest in the verification of their peroxisomal localization. Here, we present protocols used successfully in our laboratory for the detection and immunolabeling of peroxisomal proteins in cultured mammalian cells. We present immunofluorescence and fluorescence-based techniques as well as reagents to determine peroxisome-specific targeting and localization of candidate proteins.